Review of Factors on The Level of Fiscal Independence of South Borneo Province - Bayu Adji Dharmawan (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
The purpose of the study was to analyze the influence of local native income, general distribution funds, and regional financial institution-specific distribution funds in South Kalimantan Province from 2015 to 2019 on regional fiscal independence. The sample of this study is 13 districts/cities in South Kalimantan Province. The type of research used in this study is associative research that aims to find out the influence or relationship between two or more variables. This research is intended to find out the influence of local native income, general allocation funds and special allocation funds on regional fiscal independence. The data analysis method used is a statistical analysis method using SPSS 25 software. Before the data is analyzed, the classic assumption test is first performed. The results of this study showed that regional fiscal revenues, general allocation funds, and special allocation funds cooperated in the region's level of financial independence. Some regional fiscal revenues negatively impact regional fiscal independence, general allocation funds have a positive impact on regional fiscal independence, and special allocations negatively impact regional fiscal independence.